SULFUR DIOXIDE INTERACTION WITH MONOETHANOLAMMONIUM AND POLYETHYLENEPOLYAMMONIUM CITRATES AQUEOUS SOLUTIONS PRODUCTS COMPOSITION AND THE RELATIVE STABILITY - Khoma, Ruslan; Vodzinskii, Sergey; Bienkovska, Tetyana (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2025)
The paper presents the results of pH, redox, and conductometric studies on the acid-base interaction during sulfur dioxide chemisorption by aqueous solutions containing 0.1 mol/L monoethanolammonium (MEA·1/3CA) and polyethylenepolyammonium (PEPA·1/3CA) citrates, as well as buffer solutions of monoethanolamine–monoethanolammonium citrate (MEA·1/6CA) and polyethylenepolyamine–polyethylenepolyammonium citrate (PEPA·1/6CA), in comparison with sodium citrate. The composition of the compounds formed during SO2 absorption by Na3Cit, MEA·1/3CA, PEPA·1/3CA, MEA·1/6CA, and PEPA·1/6CA solutions at 273–313 K was determined.For the same amount of absorbed sulfur dioxide, an increase in specific electrical conductivity (æ) with rising temperature was observed in SO2–Na3Cit–H2O and SO2–MEA×1/3CA–H2O solutions within the 273–313 K range. However, in the SO2–MEA×1/3CA–H2O, SO2–PEPA×1/3CA–H2O, SO2–MEA×1/6CA–H2O, and SO2–PEPA×1/6CA–H2O systems, a decrease in Δæ was noted upon heating to 303 K, which is attributed to their ion-molecular composition. Based on developed mathematical models, the ion-molecular component composition of SO2–MEA×1/3CA–H2O and SO2–MEA×1/6CA–H2O solutions was determined at 283–313 K. The concentration and thermodynamic constants for the formation of ionic associates were calculated:(NH3CH2CH2OH)2SO3, H3CH2CH2OH{HOC3H4(COOH)2(COO-)} (Ia), {H3CH2CH2OH}2{HOC3H4(COOH)(COO-)2} (IIa), {H3CH2CH2OH}2{HOC3H4(COOH)2(COO-)} (IIb), {H3CH2CH2OH}3{HOC3H4(COO-)3} (IIIa), as well as ion-molecular associates:H3CH2CH2OH{HOC3H4(COOH)3} (Ib), {NH2CH2CH2OH}3{H3CH2CH2OH}3{HOC3H4(COO-)3} (IVa), {NH2CH2CH2OH}2{H3CH2CH2OH}4{HOC3H4(COO-)3} (IVb). In SO2–MEA×1/3CA–H2O solutions, as the temperature increases, bond rearrangement occurs in ionic associates IIa and Ib, as indicated by the absence of a clear temperature dependence ofp, along with the strengthening of IIa and Ib. Conversely, in SO2–MEA×1/6CA–H2O solutions, increasing temperature leads to the weakening of the bonds in compounds Ia, IIIa, IVa, and IVb, while in compound Ib, the bonds strengthen.